2014
DOI: 10.1021/ol500361w
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Oriented Asymmetric Catalysis (DOAC): Stereochemically Divergent Synthesis of Thiochromanes Using an Imidazoline–Aminophenol–Nickel-Catalyzed Michael/Henry Reaction

Abstract: The (S,S)-diphenylethylenediamine-derived imidazoline-aminophenol-Ni complex catalyzed tandem asymmetric Michael/Henry reaction of 2-mercaptobenzaldehydes with β-nitrostyrenes to give the corresponding (2S,3R,4R)-2-aryl-3-nitrothiochroman-4-ols in up to 99% diastereoselectivity with 95% ee was demonstrated in diversity-oriented asymmetric catalysis. Reduction of the nitro group of the chiral thiochromanes gave a new series of (2S,3R,4R)-3-amino-2-arylthiochroman-4-ols with retention of the strereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…The scope was substantial, and high yields were generally obtained for substrates having various substitutions. Only transproducts were observed in the [4 + 1] annulations (> 99:1 dr, entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It appeared that the substitution patterns, regardless of the positions or electronic natures on the aromatic ring (R 1 , R 2 or Ar), had little effect on the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope was substantial, and high yields were generally obtained for substrates having various substitutions. Only transproducts were observed in the [4 + 1] annulations (> 99:1 dr, entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It appeared that the substitution patterns, regardless of the positions or electronic natures on the aromatic ring (R 1 , R 2 or Ar), had little effect on the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[1] As such, efficient and practical synthetic methods to establish complementary diastereoselectivity in one-pot reactions from simple materials have rarely been explored. [2] The most practical solutions to diastereodivergence from the same starting materials often rely on catalysts, especially chiral catalysts, [3][4][5][6][7] because the use of controls such as substrates, temper-ature, and solvents for complementary diastereoselectivity has been a longstanding challenge. [8] In addition, chemoselective transformations open up a new avenue for the construction of complex molecules in synthetic organic and medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions occur with bimetallic activation and exhibit relatively low catalyst loading. Other catalytic systems have recently been reported that provide additional examples of the challenges and opportunities that exist in this area [155,179].…”
Section: Michael Reactionsmentioning
confidence: 99%
“…[6a] An exo'-selective enantioselective cyclization also has been achieved using a chiral IAP/Ni catalyst. [9,10] This strategy allows synthesis of pyrrolo [3,4-b]indole derivatives, [11,12] having a quaternary carbon center, which are structural isomers of cyclotryptamines. [9,10] This strategy allows synthesis of pyrrolo [3,4-b]indole derivatives, [11,12] having a quaternary carbon center, which are structural isomers of cyclotryptamines.…”
mentioning
confidence: 99%